Emotions Affect Every Decision You Make (But That's a Good Thing) - Young, Stephanie (Canadian Perspectives on Academic Integrity, 2023)
In Western societies, adjudication has long been said to involve the crucial task of putting one’s emotions aside. This so-called dispassionate approach is assumed to result in impartial decision-making vis-à-vis the provision of natural justice and procedural fairness. However, recent research findings on emotions and decision-making do not accord with this assumption. Overall, this body of research, which has grown exponentially over the past 30 years, suggests that emotions cannot be sifted out from decision-making processes. Thankfully, this research also supports the argument that human emotion is a precondition for enacting justice. There are multiple ways that specific emotions can ultimately influence judgment and cognitive strategies can be used to ensure that emotions are leveraged for good (i.e., outcomes in the students’ best interest). Post-secondary institutions have an ethical obligation to support adjudicators in carrying out this emotional work, and the first step is ensuring that adjudicators have comprehensive training on the findings of decision-making research. This professional development session will foster a discussion around this research and, more specifically, focus on strategies for guiding the effects of one’s emotions within the adjudication context.